The Influence of Financial Literacy and Financial Socialization on the Financial Management Behavior of Investors in Indonesia After the Covid 19 Pandemic - Muhamad Syahwildan; Erin Soleha (PT FORMOSA CENDEKIA GLOBAL, 2023)
Financial intelligence is a term used to describe the capacity to organize and manage money that is determined as one of the indicators of a person's success in managing their finances. Maximizing the value of money that a person has is being able to manage their finances well. In addition, good money management will protect a person from possible difficulties that occur. The purpose of this study is to determine the effect of financial literacy and financial socialization on the financial management behavior of investors in the Greater Bekasi area after the Covid-19 pandemic. This study uses a quantitative approach and data sources from distributing questionnaires to all investors in the Greater Bekasi area as many as 100 respondents to determine the impact of financial literacy and financial socialization on the financial management behavior of investors in the Greater Bekasi area after the Covid-19 pandemic. With the help of the SmartPLS software program and testing the outer model and inner model, data analysis was carried out using the SEM method. The results of this study indicate that financial literacy and financial socialization have an influence on financial management behavior, with P-values of 0.000 and 0.093, respectively